2014
DOI: 10.1007/s12199-014-0421-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of child and adolescent injury mortality in Japan, 2000–2010

Abstract: Objective Injury is the leading cause of death among children and adolescents in Japan. Despite this, until now there has been comparatively little research on this phenomenon. The purpose of this study was to examine if there was seasonal variation in child and adolescent injury mortality in Japan in 2000-2010. Methods Vital statistics injury mortality data were obtained from the Ministry of Health, Labour and Welfare of Japan. The seasonality of the major causes of unintentional injury (transport accidents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 26 publications
2
28
1
1
Order By: Relevance
“…However, a significant single-peak cyclic trend in mortality rates was found for deaths from road accidents and drowning in July, which is the holiday season. A similar summer peak for traffic accidents, childhood drowning, and adolescent injury mortality was observed in Japan by Shinsugi and colleagues [23].…”
Section: Comparisons With Other Studiessupporting
confidence: 74%
“…However, a significant single-peak cyclic trend in mortality rates was found for deaths from road accidents and drowning in July, which is the holiday season. A similar summer peak for traffic accidents, childhood drowning, and adolescent injury mortality was observed in Japan by Shinsugi and colleagues [23].…”
Section: Comparisons With Other Studiessupporting
confidence: 74%
“…where π,π 0 is the observed and expected proportion (i.e. the average assuming no variations) of injury deaths in a specific time interval, respectively, and n is the total number of injury deaths for the entire study period [9,11,12].…”
Section: Based On the School Calendar Announced By Department Of Educmentioning
confidence: 99%
“…Previous studies showed children injury mortality may vary seasonally. Shinsugi et al [9] observed a summer peak for transport accidents and drowning mortality and more deaths in winter for asphyxia in Japanese children. However, few recent and comprehensive studies have examined the differences in under-15 children mortality by day of the week, school term and holidays.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations